Development of sandwich ELISA and lateral flow assay for the detection of Bungarus multicinctus venom. - Ji-Fei Nong; Zhou Huang; Zheng-Zhuang Huang; Jie Yang; Jin-Cheng Li; Feng Yang; Dong-Ling Huang; Fan Wang; Wei Wang (PLoS Neglected Tropical Diseases, 2023)
Snakebite envenoming adversely affects human health and life worldwide. Presently, no suitable diagnostic tools for snakebite envenoming are available in China. Therefore, we sought to develop reliable diagnostic tests for snakebite management. We conducted affinity purification experiments to prepare species-specific antivenom antibody (SSAb). In brief, affinity chromatography with an antibody purification column (Protein A) was conducted to purify immunoglobulin G from Bungarus multicinctus (BM) venom hyperimmunized rabbit serum. The cross-reactive antibodies were removed from commercial BM antivenin by immune adsorption on the affinity chromatography columns of the other three venoms, Bungarus Fasciatus (FS), Naja atra (NA), and O. hannah (OH), generating SSAb. The results of western blot analysis and enzyme-linked immunosorbent assay (ELISA) showed the high specificity of the prepared SSAb. The obtained antibodies were then applied to ELISA and lateral flow assay (LFA) to detect BM venom. The resulting ELISA and LFA could specifically and rapidly detect BM venom in various samples with the limits of quantification as 0.1 and 1 ng/ml, respectively. This method could effectively detect snake venom in experimentally envenomed rats (simulating human envenomation), which could distinguish positive and negative samples within 10-15 min. This method also showed promise in serving as a highly useful tool for a rapid clinical distinguishing of BM bites and rational use of antivenom in emergency centers. The study also revealed cross-reactivity between BM and heterogenous venoms, suggesting that they shared common epitopes, which is of great significance for developing detection methods for venoms of the snakes belonging to the same family.